Wpływ doświadczenia na proces lektury czytelnika. Refleksje dydaktyczne - Myrdzik, Barbara (Postscriptum Polonistyczne, 2020)
The author of the article presents the concept of experience and experiencing in the field of Polonistic education. According to the scholar, HansGeorg Gadamer’s philosophical hermeneutics can serve as an inspiring context in research and educational work of a teacher. Gadamer’s hermeneutics has been one of the influential ideas in philosophy and social sciences in recent years. The type of experience presented by the philosopher, that is more like a meeting, a talk than only a live stream, and whose task is to activate and rationalize what is primary in the process of common experiencing the world, can be used in school education in many ways